Coordinated investigation of midlatitude upper mesospheric temperature inversion layers and the associated gravity wave forcing by Na lidar and Advanced Mesospheric Temperature Mapper in Logan, Utah. Issue 7 (7th April 2014) - Yuan, Tao; Pautet, P.‐D.; Zhao, Y.; Cai, X.; Criddle, N. R.; Taylor, M. J.; Pendleton, W. R.
Abstract: Mesospheric inversion layers (MIL) are well studied in the literature but their relationship to the dynamic feature associated with the breaking of atmospheric waves in the mesosphere/lower thermosphere (MLT) region are not well understood. Two strong MIL events (Δ T ~30 K) were observed above 90 km during a 6 day full diurnal cycle Na lidar campaign conducted from 6 August to 13 August Logan, Utah (42°N, 112°W). Colocated Advanced Mesospheric Temperature Mapper observations provided key information on concurrent gravity wave (GW) events and their characteristics during the nighttime observations. The study found both MILs were well correlated with the development and presence of an unstable region ~2 km above the MIL peak altitudes and a highly stable region below, implicating the strengthening of MIL is likely due to the increase of downward heat flux by the enhanced saturation of gravity wave, when it propagates through a highly stable layer. Each MIL event also exhibited distinct features: one showed a downward progression most likely due to tidal‐GW interaction, while the peak height of the other event remained constant. During further investigation of atmospheric stability surrounding the MIL structure, lidar measurements indicate a sharp enhancement of the convective stability below the peak altitude of each MIL. We postulate that the sources of these stable layers were different; one was potentially triggered by concurrent large tidal wave activity and the other during the passage of a strong mesospheric bore. Key Points: The mesospheric temperature inversion is formed by gravity wave breaking The wave breaking due to enhanced saturation and statically unstable region Tidal wave and mesospheric bore induce sharp increase of stability